Green finance mechanisms and the impact on the sustainbility reporting of Small and Medium Enterprises (SMEs) - Erna Retna Rahadjeng; Chalimatus Sa'diyah; Novi Puji Lestari; Iva Khoiril Mala (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Sustainability reporting is an important issue for micro, small, and medium enterprises (MSMEs), particularly in the food and beverage, manufacturing, and agriculture sectors. Its quality and credibility depend not only on financial resources and innovation capability but also on structured, rational, and environmentally oriented investment decision-making. This study examines the effect of green finance, green innovation, and green technology on MSME sustainability reporting, both directly and indirectly through green investment decision-making. Using a quantitative approach, data were collected from 300 MSME owners and analyzed with Structural Equation Modeling (SEM) using AMOS. The results show that green finance, green innovation, and green technology have a positive and significant effect on sustainability reporting, both directly and through the mediation of green investment decision-making. These findings indicate that improving the quality and credibility of sustainability reporting requires not only access to green resources and innovation capabilities but also well-planned green investment decisions. This study highlights the importance of integrating financial resources, innovation, technology adoption, and environmentally oriented investment decision-making to strengthen sustainability reporting practices. Therefore, MSME managers are encouraged to develop systematic green investment mechanisms to improve the effectiveness and substance of sustainability reporting.